Hybrid Heme Peroxidases from Rice Blast Fungus Magnaporthe oryzae Involved in Defence against Oxidative Stress - Marcel Zámocký; Anna Kamlárová; Daniel Maresch; Katarína Chovanová; Jana Harichová; Paul G. Furtmüller (MDPI AG, 2020)
Hybrid B heme peroxidases are recently discovered unique oxidoreductases present solely in the fungal kingdom. We have investigated two typical representatives from Magnaporthe oryzae-one of the most dangerous phytopathogens known as a causal agent of the rice blast disease. First, we focused on native expression of two detected hyBpox paralogs by the means of reverse-transcription quantitative real-time PCR. Our results indicate a 7-fold induction of the MohyBpox1 transcript in a medium with H2O2 and a 3-fold induction in a medium with peroxyacetic acid. For the MohyBpox2 paralog the induction patterns were up to 12-fold and 6.7-fold, respectively. We have successfully expressed the shorter gene, MohyBpox1, heterologously in Pichia pastoris for detailed characterization. Observed biochemical and biophysical properties of the highly purified protein reveal that a typical HyBPOX is significantly different from previously investigated APx-CcP hybrids. This newly discovered secretory peroxidase reveals a Soret maximum at 407 nm, Q bands at 532 and 568 nm, CT band at 625 nm and a purity number of 1.48. Electron paramagnetic resonance (EPR) analysis suggests a mixture of high and low spin species in the ferric state dependent on calcium contents. Steady-state kinetic data reveal the highest peroxidase activity with ABTS, 5-aminosalycilate and efficient oxidation of tyrosine. MoHyBPOX1 as a fusion protein consists of two domains. The longer conserved N-terminal peroxidase domain is connected with a shorter C-terminal domain containing a carbohydrate binding motif of type CBM21. We demonstrate the capacity of MoHyBPOX1 to bind soluble starch efficiently. Potential involvement of hybrid peroxidases in the pathogenicity of M. oryzae is discussed.